Barriers about double carbon-nitrogen bond in imine derivatives (aldimines, oximes, hydrazones, azines) - Blanco, Fernando (Array, 2009)
Summary: The paper presents the results referring to the inversion mechanism of imines and their derivatives (hydrazones, oximes, azines). The calculated barriers [B3LYP/6-311++G(d,p) and G3B3)] are in good agreement with the scarce existing data. The transition states correspond in all cases to a pure nitrogen inversion except in the case of azines where they have some rotation character. The electron properties of the minima and the transition states have been characterized, allowing explanation of the geometrical changes observed in the process